Shivani Carriers Pvt. Ltd. : managing employee motivation at the bottom of the pyramid - Sharda, Kirti, (SAGE Knowledge. Cases., 2016)
Vandana Laddha, Director - Driver Management and Fleet Operations at Shivani Carriers Pvt. Ltd., cleared her desk for the day and took a deep sigh. It was another day filled with a littany of complaints from her drivers, mostly centred around their compensation. For the last few weeks, she had been nagged with worries about the effectiveness of the driver management system, which had been implemented under her leadership over the last one year. She knew that discontent was brewing among drivers, especially, the modification of the special incentive scheme, which was designed to boost productivity, seemed to be the sore point. She had been thinking about what could be done to keep the truck drivers motivated.